What is our duty to nature? - Rolston, Holmes, 1932-2025, author; Sinauer Associates, publisher (Colorado State University. Libraries, 2004)
Environmental ethics seeks appropriate respect for values in and duties regarding nature. If people have a right to life, they have a right to a quality environment. Further, environmental ethics becomes more inclusive, concerned about whales, whooping cranes, ancient forests, Earth threatened by global warming. Science alone does not teach us what we most need to know about nature: how to value it. Still, biology confronts every biologist with an urgent moral concern: caring for life on Earth. Ought not biologists above all celebrate Earth's biodiversity?
Keywords: biodiversity; conservation; environmental ethics; environmental values